Sotos Syndrome, Isolated Left Ventricular Non Compaction Cardiomyopathy and Ventricular Pre Excitation: A Case Report. - Marco Sassara; Massimo Ruggiero; Francesco Tota; Sergio Musc; Gabriella Bulzis; David Rutigliano; Giulia Frasso; Mariangela Carbone; Maria Tesorio; Pietro Scicchitano; Pasquale Caldarola; Marco Matteo Ciccone (Journal of Hypertension and Cardiology, 2013)
We report the case of a 22 year-old-male patient affected by Sotos syndrome was preoperatively and urgently evaluated for tracheal stent implantation due to respiratory insufficiency caused by idiopathic tracheal stenosis. Rest electrocardiogram detected a ventricular pre excitation; a transthoracic echocardiography showed a classic pattern fulfilling criteria for isolated left ventricular non compaction. At the best of our knowledge this is the first report of a patient suffering from Sotos syndrome and simultaneously affected by isolated left ventricular non compaction and ventricular pre excitation.
Keywords: Sotos Syndrome